Protein bioscreening of perspective form of bean (Eurasian Journal of Ecology, 2016)
The role of agricultural products is large in getting food raw materials . The bean seeds is unique on the chemical composition and included in the group of important products that provide complete protein population . Lectins areproteins of non-enzymatic nature relating to the class of glycoproteins and possessing property , and specifically bind carbohydrate ligands back biopolymers. Research will help to identify new sources of protein components to investigate their effect on different cell models , the development of biotechnological approaches their isolation and further use forthe production of plant protection products , also well as medicine and diagnostics .
Keywords: lectin bioscreening; gemmaglyutination; agglutination of erythrocytes; accessions